2018
DOI: 10.1080/19476337.2018.1440007
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocessing of wheat (Triticum aestivumcv. Kronstad) bran from Northwest Mexico: effects on ferulic acid bioaccessibility in breads

Abstract: Evaluating the biological potential of wheat grain cultivated in northwestern Mexico is important because it mainly varies according to the cultivar and production area. The aim of the present study was to evaluate ferulic acid (FA) bioaccessibility in breads supplemented with bioprocessed bran. Bran that was bioprocessed with xylanase enzyme (EB), yeast fermentation (FB), and a combination of both treatments (FEB) showed a higher total phenol content and antioxidant capacity compared with native bran (NB), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The increase of ferulic acid bioaccessibility after fermentation was also observed by Villalva et al [60] in bread supplemented with bioprocessed bran. One more example of efficacy of the raw material pre-treatment by fermentation on antioxidant compound content is reported by Rashid et al [61] who found an increased concentration of ferulic acid, organic acids, γ-oryzanol and α-tocopherol in rice bran.…”
Section: Resultssupporting
confidence: 77%
“…The increase of ferulic acid bioaccessibility after fermentation was also observed by Villalva et al [60] in bread supplemented with bioprocessed bran. One more example of efficacy of the raw material pre-treatment by fermentation on antioxidant compound content is reported by Rashid et al [61] who found an increased concentration of ferulic acid, organic acids, γ-oryzanol and α-tocopherol in rice bran.…”
Section: Resultssupporting
confidence: 77%
“…The cell wall degrading enzymes method for the mobilization of bioactive molecules in the bran fraction represents a new pathway for grain enrichment and, in addition, enhances their level in cereal flour [ 181 , 186 ]. For example, ferulic content in bread supplemented with enzymatically treated bran was higher compared to untreated bran, therefore the enzymatically treatment increased the bioaccessibility of ferulic acids [ 187 ].…”
Section: Bioavailabilitymentioning
confidence: 99%
“…Encapsulation of phenolic compounds can sustain their stability during food processing and digestion, as well as enhance their absorption and extend their life in the bloodstream, resulting in improved bioavailability [ 187 , 205 , 206 , 207 ], therefore several studies have underlined nanocarriers as a good strategy to improve bioavailability of phenolics [ 208 , 209 , 210 , 211 ], such as lipid nanocarriers [ 212 ]. In 2017, Hu et al [ 213 ] reviewed and analyzed in depth the encapsulation technology processes of phenolic compounds and their impact on bioavailability, where the main conclusions underlined the idea that nanocarriers may increase the bioavailability of phenolic compounds, mainly by enhancing their solubility, protecting from degradation in the intestinal tract, supporting the permeation rate in the small intestine, and, moreover increasing their contents in the bloodstream.…”
Section: Bioavailabilitymentioning
confidence: 99%
“…Feruloyl esterase and pentopan have been shown to release ferulic acid from wheat bran selectively, and pretreatment of the bran with alcalase and termamyl enhanced ferulic acid production by up to 20 times ( Ferri et al, 2020 ). Bread enriched with bioprocessed wheat bran through xylanase enzyme and yeast fermentation improved ferulic acid bio-accessibility ( Amaya Villalva et al, 2018 ). Furthermore, wheat aleurone fractions treated with xylanase alone or in combination with feruloyl esterase improved ferulic acid bioavailability in obese mice fed a high-fat diet.…”
Section: Bioprocessing Applications To Attain Optimum Phenolic Compounds In Cerealsmentioning
confidence: 99%